The Effect of Green Marketing on Buying Interest in Ms Glow Products in Lamongan City With E-Wom as a Mediation Variable - Utami Utami; Evi Fitrotun Najiah; Mohammad Yaskun (Sean Institute, 2024)
The purpose of the research is to find out the impact of the MS Glow Markleting Grleen Markleting in the city of Lamongan with e-WOM as a variety of mlediation labels. Jelnis research ylang inli adlalah quantitative. The research population of this research forgot about the MS Glow consulate in the Lamonlgan district. The sample used in this study was 264 respondents. The results of the investigation showed that balhwa varliabel greeln malrketing had a potential ylang lure and a signal to be exposed to milnat belli clones. The green marketing variable has a positive and significant effect on e-WOM. The e-WOM variable has a positive and significant effect on buying interest. The green marketing variable has a positive and partial significance effect, as well as mediated by e-WOM on the buying interest of MS Glow consumers in Lamongan.